Targeting cell cycle protein in gastric cancer with CDC20siRNA and anticancer drugs (doxorubicin and quercetin) co-loaded cationic PEGylated nanoniosomes - Hemati M (Dove Medical Press, 2019)
Mahdie Hemati,1,2 Fateme Haghiralsadat,2,3 Farzaneh Jafary,1 Seyedmohammad Moosavizadeh,4 Ali Moradi11Department of Clinical Biochemistry, Faculty of Medicine, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 2Medical Nanotechnology and Tissue Engineering Research Center, Yazd Reproductive Sciences Institute, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 3Department of Advanced Medical Sciences and Technologies, School of Paramedicine, Shahid Sadoughi University of Medical Sciences, Yazd, Iran; 4Department of Laboratory Sciences, School of Paramedicine, Shahid Sadoughi University of Medical Sciences, Yazd, IranBackground and purpose: In a past study, we developed and optimized a novel cationic PEGylated niosome containing anticancer drugs (doxorubicin or quercetin) and siRNA. This study intended to evaluate the anti-tumor effects of the combination therapy to target both the proteins and genes responsible for the development of gastric cancer. CDC20, known as an oncogene, is a good potential therapeutic candidate for gastric cancer.Methods: In order to increase the loading capacity of siRNA and achieve appropriate physical properties, we optimized the cationic PEGylated niosome in terms of the amount of the cationic lipids. Drugs (doxorubicin and quercetin) and CDC20siRNA were loaded into the co-delivery system, and physical characteristics, thermosensitive controlled-release, gene silencing efficiency, and apoptosis rate were determined.Results: The results showed that the designed co-delivery system for the drugs and gene silencer had an appropriate size and a high positive charge for loading siRNA, and also showed a thermosensitive drug release behavior, which successfully silenced the CDC20 expression when compared with the single delivery of siRNA or the drug. Moreover, the co-delivery of drugs and CDC20siRNA exhibited a highly inhibitory property for the cell growth of gastric cancer cells.Conclusion: It seems that the novel cationic PEGylated niosomes co-loaded with anticancer drug and CDC20siRNA has a promising application for the treatment of gastric cancer.Keywords: niosome, siRNA, CDC20, doxorubicin, quercetin